Relationships between geomagnetic Ар-indeх and parameters of the immunity in patients with neuroendocrine-immune complex dysfunction in former sportsmen - Tserkovniuk, Ruslan; Yanchij, Roman; Plyska, Oleksandr; Kovbasnyuk, Marta; Chendey, Ivanna; Hagner-Derengowska, Magdalena; Zukow, Xawery; Kałużny, Krystian; Muszkieta, Radosław; Zukow, Walery (Journal of Education, Health and Sport, 2021)
Background. The effect of geomagnetism on human immunity has so far been studied through long-term observations. Recently, we have been detected the immediate immunotropic effects of the disturbances of the geomagnetic field (Ap-index) at multiple sclerosis patients. The aim of this study was to identify the immunotropic effects of geomagnetism on another contingent of people. Material and methods. The object of observation were 21 men (24-63 y) and 20 women (33-62 y) with neuroendocrine-immune complex dysfunction. Each patient was tested twice with an interval of 4 days. Observations were carried out on 09.06. and 13.06. 2015, 14.09 and 18.09. 2015, 27-28.03. and 04-05.04. 2018, 28.01. and 01.02. 2019. Retrospectively we recorded the geomagnetic Ap-Index on the day of testing and during the previous 7 days, using resource https://www.spaceweatherlive.com/. The content of subpopulations of lymphocytes expressing CD3, CD4, CD25, CD8, CD22 and CD56 receptors as well as the serum concentration of circulating immune complexes, immunoglobulins classes M, G, A, C-reactive protein and IL-1β was determined. The state of phagocytic function of neutrophils estimated by microbial count and phagocytic and killing indices against Staphylococcus aureus and Escherichia coli. Results. During the week, the average level of Ap-index ranged from 7 to 13 nT. Maximum coefficients of multiple correlation with immunity parameters were detected for Ap-index on the eve of blood sampling (R=0,768) and 5 days before it (R=0,758) while the minimum on 3 (R=0,541) and 2 (R=0,479) days before sampling. The canonical correlation between Ap-indices for 7 days before and on the day of testing, on the one hand, and the immunity parameters - on the other hand, was very strong: R=0,921; R2=0,849; χ2(200)=375; p<10-6. Conclusion. Disturbances of the geomagnetic field (Ap-index) has a significant immediate modulating effect on the immune parameters, mostly phagocytosis completeness, Igg A and M serum concentration, T-helper and B lymphocytes as well as eosinophils, rod-shaped neutrophils and monocytes blood level.